Peran Hukum Internasional dalam Penanganan Perubahan Iklim: Studi Meta-Analisis terhadap Kesepakatan Paris - Musrifah; Syarifah, Hanni Naylatus; Saputra, Adit (Universitas Sains dan Teknologi Komputer, 2024)
Climate change poses a significant global challenge requiring robust international legal frameworks to ensure effective mitigation and adaptation. This study examines the role of international law in implementing the Paris Agreement, focusing on the challenges and opportunities of its bottom-up approach to Nationally Determined Contributions (NDCs). Utilizing a meta-analytic methodology, the research synthesizes findings from 30 scholarly articles and policy documents to identify critical patterns and gaps. The findings reveal disparities between developed and developing nations in achieving NDC targets, driven by differences in financial and technological capacities. Developed nations exhibit higher success rates due to better infrastructure and funding, while developing nations struggle with significant barriers such as limited access to climate finance and bureaucratic inefficiencies. Additionally, the study underscores the importance of accountability and transparency mechanisms, such as the Enhanced Transparency Framework (ETF), in fostering international cooperation. The study recommends reforms in global climate finance, enhanced institutional capacity in developing countries, and stronger collaborations for technology transfer. By addressing these gaps, the Paris Agreement can serve as a more effective platform for global climate action. The findings contribute to the broader discourse on climate governance and provide actionable insights for policymakers and international stakeholders.